2016
DOI: 10.1245/s10434-016-5294-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Interval between Neoadjuvant Chemoradiotherapy and Surgery in Rectal Cancer Patients: A Population-Based Study

Abstract: Background Neoadjuvant chemoradiation therapy (CRT) has been widely implemented in the treatment of rectal cancer patients, but optimal timing of surgery after neoadjuvant therapy is unclear. The purpose of this study was to evaluate the effects of prolonged intervals between long-course CRT and surgery in rectal cancer patients.MethodsData on all rectal cancer patients diagnosed between 2006 and 2011 were retrieved from the population-based Netherlands Cancer Registry; the main outcome parameters were patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 33 publications
1
47
1
1
Order By: Relevance
“…The pCR rate of 5% in the present study is less than the 10–27% rate reported in larger series which included T2 and T3 rectal cancers and T4 tumours not needing MVR . Also the interval of 6–8 weeks between the end of CRT and surgery may have influenced the pCR rate, since an interval of 9–12 weeks results in a higher rate of achieving a pCR . There is contrary evidence to suggest that the pathological response decreases again after 9–10 weeks .…”
Section: Discussioncontrasting
confidence: 91%
“…The pCR rate of 5% in the present study is less than the 10–27% rate reported in larger series which included T2 and T3 rectal cancers and T4 tumours not needing MVR . Also the interval of 6–8 weeks between the end of CRT and surgery may have influenced the pCR rate, since an interval of 9–12 weeks results in a higher rate of achieving a pCR . There is contrary evidence to suggest that the pathological response decreases again after 9–10 weeks .…”
Section: Discussioncontrasting
confidence: 91%
“…A meta‐analysis of 13 studies and 19 652 patients published in 2017 revealed similar sphincter preservation rates between shorter and longer interval groups (relative risk 0.99, P = 0.743) . Similarly, in a Dutch study, sphincter preservation rate did not significantly differ in longer interval groups ranging between 5 and 14 weeks ( P = 0.393) . Briefly, the recently published data show no beneficial effect of longer intervals on sphincter preservation .…”
Section: Discussionmentioning
confidence: 84%
“…). A total of 26 publications, including four RCTs and 25 445 patients with rectal cancer were eligible for inclusion ( Table ). Twenty‐four of the 26 studies (22 650 patients) reported the primary endpoint of pCR based on the predefined wait interval and were included in the qualitative and quantitative analysis for this outcome variable; 15·9 per cent (1522 of 9551) and 11·3 per cent (1481 of 13 099) had achieved pCR in the extended and classical intervals respectively.…”
Section: Resultsmentioning
confidence: 99%